Visual narratives of division in contemporary Palestinian art and social space - Baasch, Rachel Mary (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
This study analyses artworks by contemporary Palestinian artists that respond to visual narratives of division in social space from a perspective grounded in a South African context. The state of Israel is built on Historic Palestine. Political Zionism has created an ideological narrative of division that positions people of the Jewish faith as the rightful heirs to the land on which Palestinians have lived for centuries. In order to execute their vision of an exclusively Jewish nation state, the founding pioneers of political Zionism colonised and ethnically cleansed Historic Palestine, establishing Israel in 1948. To sustain the exclusive claim to Palestinian land, Israel has divided the space and the people in it at every possible level. The greatest testament to these efforts is the Israeli apartheid wall and checkpoint security system that can be described as a monumental visual narrative of division. With each second that passes, Israel claims more Palestinian land and expands on existing fences, walls and barriers. It is no secret that the Occupied Palestinian Territories are rapidly transforming into open-air prisons. Israel has stolen the Palestinian horizon line and replaced it with a concrete wall that blocks out light, vision and optimism. Within the shadows of these conflicted, traumatised sites of division, Palestinian artists seek openings, cracks and loopholes that signal the possibility for physical and psychological transgression of these seemingly impenetrable structures of division. I have developed a creative methodology that can be understood through the metaphor of 'looking with the skin' as a way to identify and analyse visual narratives of division and artistic responses to sites of division in Palestinian social space. Looking with the skin combines aspects of participant observation (specifically the emphasis on engaged fieldwork) from the discipline of Anthropology with the method of visual analysis from the discipline of Art History. In my application of this method through primary fieldwork conducted within the Occupied Palestinian West Bank Territory from 2013 and 2014, I have learnt that Israel's colonisation, military occupation and system of apartheid directly impacts the ability of Palestinian artists to make and disseminate their work as well as the choice of content within their artwork. The artworks analysed in this thesis by the artists Khaled Jarrar, Y ael Bartana, Larissa Sansour, Hasan Darahgmeh, Fareh Saleh and Emily Jacir can be positioned in relation to artworks by artists based within a South African context, namely Thando Mama, Serge Alain Nitegeka and Doung Anwar Jahangeer. In this thesis I present a combination of my own photographic documentation of sites of division with the West Bank OPT in relation to the specific artworks made by the artists mentioned above. In my analysis of the photographic documentation and the artists' work I highlight similarities, parallels, threads and intersecting narratives that connect different artists to one another and to the sites of division they are responding to within their artistic practice. This study carves a small conceptual pathway through ideological and physical walls from South Africa to Palestine through the study of contemporary art and visual culture.
Keywords: Art, Palestinian Arab; Art, Palestinian Arab -- Political aspects; Art and society -- Palestine